SIKAP ILMIAH SISWA DALAM BELAJAR BIOLOGI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS PROYEK PADA MATERI DAUR ULANG LIMBAH ORGANIK KELAS X SMA N 1 LIRIK TAHUN AJARAN 2013/2014 - Sri Wahyuni Wahyuni; Yustina '; Evi Suryawati Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:A descriptive study has been conducted to determine students’ scientific attitude in biology learning with project based learning model on the topic of organic waste recycling for grade X SMAN 1 Lirik school year 2013/2014. The population of this study was grade X students of SMAN 1 Lirik school year 2013/2014 and the sample was 29 students of Xb class SMAN 1 Lirik, that consists of 8 male students and 21 female students. Parameters of this study were students’ scientific attitude and the indicators were curiosity, responsibility, collaboration, tolerationandthoroughness. Observation sheet and peers questionnaire were used as data collecting instruments. The result showed that the percentage of students’ scientific attitude obtained through observation sheet was 76,2% with good category and obtained throught peers questionnaire was 71,6% with good enough category. Based on the study that has been conducted in SMAN 1 Lirik school year 2013/2014, students’ scientific attitude has became better at biology learning with project based learning model on the topic of organic waste recycling Key words:Project Based Learning, Students’ Scientific Attitude